Reviewing the Role of Spatial Factors in Promoting Social Interactions with the Purpose of Designing a Cinematic-Cultural Complex - Karimi Azeri, Amir Reza; Haghighi Sosari, Zahra Delkhosh; Mozhdehi, Amirnezhad (Salehan Institute of Higher Education, 2018)
The first goal of architecture is to build a proper space for human activities. Having sufficient knowledge about human beings and their relationships with others can be effective in creating an environment that is appropriate for certain types of activities. On the other hand , as social creatures, humans have various qualitative and quantitative levels of social interactions; while many of the existing buildings have created a deeper gap in human relations by solely responding to the functional needs and failing to give focused attention to human factors. In fact, the subject of the current research indicates that, due to the shortage of cultural facilities and healthy urban hangouts, as well as the unacceptable quality of the existing cultural spaces especially the cinemas, the recommended design can be a multifunctional complex and have spaces with official and unofficial sociable spaces. Also, it can make creation and promotion of social interactions possible. The current research is a descriptive-analytical research in terms of nature and it is a survey, in terms of method. In addition, it is an applied research in terms of its objective, a quantitative research based on the research data and a field study based on its procedure. In this respect, some human and environmental variables that affect social interactions have been extracted from documents and library studies. Among them,Â five of the most important factors were selected as the basis of this research based on the prioritization done by specialized environmental psychologists among faculty members of some of the most well-known and valid universities in Iran. The statistical community of this research is the city of Anzali harbor and places related to active cinemas of the city. Therefore, by specifying the community, sample and tools of the research, the roles played by the selected variables in association with the confirmation and rejection of the research hypotheses were tested. After analyzing the data using SPSS software, the selected variables were prioritized as follows: capabilities of the environment, attraction, visual beauty and aesthetic dimensions, natural landscape, view and adjacency, accessibility, continuity and legibility. Then, the most effective solutions for fulfilling the research objectives were developed.